Pengaruh Pendapatan dan Pengetahuan tentang Pemberantasan Sarang Nyamuk (PSN) pada Keberadaan Jentik Aedes aegypti - Rochmadina Suci Bestari; Estu Puguh Prabancono; Listiana Masyita Dewi; Riandini Aisyah (STIKes Surya Global Yogyakarta, 2020)
ABSTRACTBackground of Study : DHF still become health problem in Indonesia. In Central Java, especially Sukoharjo district, Angka Bebas Jentik (ABJ) is still under national standard. Some factors that influence the existence of larvae are the level of income and knowledge about PSN. Consumerism triggered escalation amount of mosquito breeding sites due to ownership of non-degradable goods like plastic containers, paper cups, and so on. Consumerism is related to income. This study has purpose to determine corelation between income levels and knowledge about PSN with existence of Aedes aegypti larvae in Karangtengah Village.Methods : Designed with cross-sectional approach. The population were residences that has Family Card in Karangtengah Village with a total of 1660 households taken 65 households. The independent variable is the level of income and knowledge about PSN. Dependent variable is existence of larvae. Data analysis used Chi-Square test and contingency coefficient (C).Results : The results showed income with the existence of larvae (container index) (p = 0.009, C = 0.308) and PSN knowledge in the presence of larvae (container index) (p = 0.005, C = 0.332).Conclusion : The results of data analysis show that there is a correlation between income and knowledge about PSN with the existence of larvae. This study showed there is a relationship between income and knowledge about PSN with the existence of larvae.Keywords: Aedes aegypti, Container Index, DHF